Negara, Hak-hak Minoritas Agama, dan Multikulturalisme (Kasus Kekerasan terhadap Ahmadiyah) - Ilham Mundzir (JURNAL INDO-ISLAMIKA, 2012)
This essay attempts to discuss religious violence against Ahmadiyah adherents as the minority group, in term of religion, in Indonesia. This essay demonstrates and argues that the main factor of the rise of the violence is the failure and absence of the state in enforcing the politics of liberal multiculturalism as to govern the social plurality and diversity. It stresses that the state rather tends to establish the politics of conformity and make racial policy against minority. As a result, the agenda of universal protection toward rights of minorities is hardly realized.